2009
DOI: 10.1155/2009/952304
|View full text |Cite
|
Sign up to set email alerts
|

Novel miR390‐Dependent Transacting siRNA Precursors in Plants Revealed by a PCR‐Based Experimental Approach and Database Analysis

Abstract: TAS loci in plant genomes encode transacting small interfering RNAs (ta-siRNAs) that regulate expression of a number of genes. The function of TAS3 precursor in Arabidopsis thaliana is controlled by two miR390 target sites flanking two ta-siARF sequences targeting mRNAs of ARF transcription factors. Cleavage of the 3′-miR390-site initiates ta-siRNAs biogenesis. Here we describe the new method for identification of plant ta-siRNA precursors based on PCR with oligodeoxyribonucleotide primers mimicking miR390. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…To apply the approach based on PCR amplification [15] to TAS3-like loci of lower land plants, we designed degenerated primers BryoTAS-P and Bryo TAS-M Figure 1: Analysis of PCR products in 1.5% agarose gel. Amplification of genomic DNA sequences flanked by miR390 sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To apply the approach based on PCR amplification [15] to TAS3-like loci of lower land plants, we designed degenerated primers BryoTAS-P and Bryo TAS-M Figure 1: Analysis of PCR products in 1.5% agarose gel. Amplification of genomic DNA sequences flanked by miR390 sites.…”
Section: Resultsmentioning
confidence: 99%
“…For amplification, the Physcomitrella TAS3-specific primers [15] were used: a forward primer Bryo TAS-P 5 -GRCGYTAYCCTCYTGAGCT-3 and reverse primer Bryo TAS-M 5 -TAGCTCAGGAGTGATA(G/T)A(C/A)AA-3 . For PCR, 25-35 cycles were used for amplification with a melting temperature of 95…”
Section: Analysis Of Nucleic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, only the 39 miRNA target site in the TAS3 transcript is cleaved, as in other flowering plants, while both miR390 complementary sites in moss and pine showed cleavage ( Figure 2B) (Axtell et al, 2006). A shorter variant of TAS3 than that found in Arabidopsis is also conserved in many eudicots and is found alongside the canonical TAS3 locus; this variant has cleavable target sites at both 59 and 39 positions and includes only a single tasiARF (Figure 2A) (Krasnikova et al, 2009;Xia et al, 2012). A recent study of phasiRNA trigger evolution (e.g., miRNAs) across a broad range of plant (A) As the first step in secondary siRNA biogenesis, mRNA targets are cleaved by a miRNA.…”
Section: Overview Of Tasirna Biogenesis Function and Diversificatiomentioning
confidence: 91%
“…The two-hit model provided the first mechanistic insights into the process for tasiRNA biogenesis, describing TAS3 as the prototypical two-hit locus (Axtell et al, 2006). Early experimental examination of the two TAS3 target sites demonstrated that miR390 has an unusual association with AGO7 that is important for tasiRNA biogenesis and that the 59 proximal miR390 target site must not be cleaved (Montgomery et al, 2008a), although outside of Arabidopsis, TAS3 variants may be cleaved at the 59 position (Axtell et al, 2006;Krasnikova et al, 2009;Xia et al, 2012). However, more recent data from other plant genomes describe two-hit loci for which the miRNA triggers are believed to be AGO1 associated and for which the 59 proximal site may be cleaved.…”
Section: Mirna Triggers Of Phased Secondary Sirnasmentioning
confidence: 99%